God as Intellect in the philosophical Theology of Plato, Aristotle and Plotinus - Volkova, Nadezhda (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. I, Bogoslovie, filosofii͡a, 2017)
The article gives an overview of the main stages in the development of philosophical theology in Plato, Aristotle and Plotinus, as well as its central concept - Active Intellect or God. It is shown, firstly, that Plato was the first who formulated the concept of a One omnibenevolent God. Plato opposed this doctrine to the gods of traditional mythology. In the "Timaeus" talking about the creation of the world, Plato represents God as an artisan, i. e. Demiurge, who arranges the World soul and matter with the help of the numbers. Therefore, God is introduced as an Intellect, because looking at an intelligible paradigm, he created the cosmos as its likeness. Secondly, it was shown that Aristotle made theology demonstrative theoretical knowledge. God as a subject of such knowledge is the pure actuality of thinking. Third, it is shown that Plotinus, continuing the line of Plato and Aristotle, gave philosophical theology a new, much more personal character. Theology for Plotinus is not only an demonstrative knowledge of the omnibenevolent God, but also a personal experience of reunion with him. A special attention in the article is paid for Plotinus' interpretation of the Platonic Demiurge. It is shown that Plotinus first connected the two aspects of the divine, namely the Demiurge-creator and the intelligible paradigm that are described in the "Timaeus," into the single hypostasis of Intellect. The main reason for this assertion was the necessity to postulate the unity of the intellect and the intelligible object as a necessary condition for the possibility of all cognitions. As a result, instead of the traditional idea of the two gods, Plotinus elaborates the doctrine of a single divine Intellect, combining both these aspects.